Calculation and Measurement of RFID Tag Critical Frequency - Vestenicky, Peter; Vestenicky, Martin; Palecek, Juraj (Communications - Scientific letters of the University of Zilina, 2013)
This paper deals with undesirable phenomenon in inductively coupled RFID system, i. e. by fading out the amplitude modulation of carrier signal in RFID reader. It is caused by inaccurate tuning of RFID transponder resonant circuit. The phenomenon is described by mathematical model of the inductively coupled RFID system. The numerical and graphical results of mathematical modelling is then compared by measurement of resonant frequency of real (tuneable) RFID circuit on which the amplitude modulation fades out.